Security Agents Public Perception in Nigeria: A Study on the Police and the Vigilante (Neighborhood Watch) - Aluko Opeyemi Idowu (Journal of Political Studies, 2016)
States are saddled with the responsibility of protecting the citizenry from internal insurrection and external aggression. Formal policing sector is perceived as the most appropriate security forces to mitigate civil crises within the community. In the recent times the use of the police is been joggled with the vigilante in most developing democracies. The vigilantes are seen as more effective in curbing immediate crime and deterring future crimes than the conventional police. The objective of this paper is to determine the extent of public trust for the security (police and vigilante) agents in Nigeria. The theoretical framework of Chaos theory and Tyre burning model are adopted to analyze crime while the data from Afrobarometer database and researchers' fieldwork are analyzed to see the perception of Nigerians on security and safety of their community. Policy recommendations of co-security options with basic legislation to reduce the unprofessional-ism of the security sectors are proffer.